THE LEGAL EFFECTS OF THE EUROPEAN UNION CITIZENSHIP - Oana-Mihaela SALOMIA (Challenges of the Knowledge Society)
The citizenship of the European Union is a reality or a concept? The consecration of the citizenship of the European Union by the Maastrich0t Treaty has been accompanied by the specific rights allowed to the citizens of the Member States. At the present, the Treaty on the Functioning of the European Union and the Charter of fundamental rights of the European Union mention the definition of the citizen of the European Union, the features and role of its citizenship: „Every person holding the nationality of a Member State shall be a citizen of the Union. Citizenship of the Union shall be additional to and not replace national citizenship”. In the Preamble of the Treaty on the European Union, the Member States affirm that they are „resolved to establish a citizenship common to nationals of their countries”. The Court of Justice of the European Union has stated the importance of this concept and its application in relationship with the specific rights of the citizens of the Member States: „Union citizenship is destined to be the fundamental status of nationals of the Member States”. The concept has a certain applicablility in different fields as Internal Market or European Union's area of freedom, security and justice with legal effects in terms of rights and obligations. The citizenship of the European Union does exist but its added value will be tangible at the moment when our ID cards or passports will contain a reference to that; if the citizens of the Member States express their interest in this regard and the political commitement will be evinced, the national citizenship could be replaced with the European Union citizenship on the moment of the Treaties revision’s, but, nowadays, according to art. 4. 2 of the Treaty on the European Union, „The Union shall respect the equality of Member States before the Treaties as well as their national identities, inherent in their fundamental structures, political and constitutional, inclusive of regional and local self-government”. In conclusion, the citizenship of the European Union must be analyzed in a dynamic evolution thanking into account its development, the interest and commitement of the Member States and their citizens and the future of the European Union.